Exploring Social Realities and Identity Struggles through Content Analysis of Dialogues in La Désintégration by Philippe Faucon - Stephane, Narcis (Global Journal of Cultural Studies, 2023)
This paper delves into the intricate social realities and identity struggles depicted in the film La Désintégration by Philippe Faucon through a meticulous content analysis of dialogues. This study aims to unveil the underlying sociopolitical themes embedded within the characters' dialogues by employing content analysis as the primary methodology. La Désintégration offers a poignant exploration of issues such as cultural and religious identity, socioeconomic marginalisation, and the process of radicalisation. Through a detailed analysis of selected dialogue excerpts, this paper sheds light on the characters' nuanced interactions and internal conflicts. By engaging with the dialogues as narrative devices, this research contributes to a deeper understanding of how banlieue cinema captures and reflects broader societal concerns. The findings extend the existing discourse on banlieue cinema and highlight the significance of dialogue in conveying the intricate web of social complexities in contemporary societies.